Searching for the New Behavioral Model in Energy Transition Age: Analyzing the Forward and Reverse Causal Relationships between Belief, Attitude, and Behavior in Nuclear Policy across Countries - Kim, Byoung Joon; Kim, Seoyong; Kang, Youngcheoul; Kim, Sohee (International Journal of Environmental Research and Public Health, 2022)
This study aims to analyze the forward/reverse causal relationships between belief (risk perception), attitude (judgment), and behavior (acceptance). A traditional view stresses forward causal relationships between the three variables. However, recently, several studies have reported the possibility of reverse causal relationships between them. Based on survey data collected from 1027 Korean/Japanese participants, here we test not only the forward or reverse relationships between these three variables, but also how such causal relationships depend on the trust and country contexts (Korea and Japan in this study). The results showed that, first, not only a general forward causal relationship but also reverse causal relationship exists between belief, attitude, and behavior. Second, there exist the moderated mediation and mediated moderation effect of trust in government and media across two countries. Third, the effects of trust in government and media work significantly overall. However, the patterns of interaction effects differ between two countries. The level of trust in the government influenced the belief and attitude of citizens in Japan more than in Korea. However, the level of trust in the media showed opposite results.
Keywords: Attitude; Government; Humans; Policy; Republic of Korea; Trust; comparative analysis; conflict resolution model; nuclear energy perception; the effect of trust